Facial Recognition an Added Security Level To Mobiles And Laptops (International Journal of Engineering and Computer Science, 2018)
We have been using mobiles and laptops for quite a long time, yet their security is poor. Any pattern or alpha-numeric lock can be forged by an un-authentic user. When someone wants to perform a major change in operating system’s settings they are not asked to re-authenticate the user. Our application guards the system using facial recognition